Good Corporate Governance dan Manajemen Laba Governance Memoderasi Hubungan Related Party Transaction Pada Agresivitas Penghindaran Pajak - Widiana, I Gusti Ketut Wira; Dwirandra, Anak Agung Ngurah Bagus; Budiartha, I Ketut; Putri, I Gusti Ayu Made Asri Dwija (E-Jurnal Akuntansi, 2022)
This study aims to examine the relationship of related party transactions (RPT) on aggressiveness of tax avoidance with good corporate governance and earnings management as moderating. The study was conducted in rural banks throughout Bali with a sample size of 137 rural banks. The sample was collected by using purposive sampling technique. Data collection is done through the publication of data from the Financial Services Authority (OJK). The data analysis technique used Moderated Regression Analysis (MRA). The results show that related party transactions have a negative but not significant effect on the aggressiveness of tax avoidance. While good corporate governance is not proven to reduce the aggressiveness of RPT tax avoidance and earnings management increase the influence of RPT on the aggressiveness of tax avoidance. Keywords: Management of Profit; Good Corporate Governance; Related Party Transaction; Aggressiveness of Tax Avoidance.